2002
DOI: 10.2527/2002.802357x
|View full text |Cite
|
Sign up to set email alerts
|

The provision of solid feeds to veal calves: I. Growth performance, forestomach development, and carcass and meat quality1

Abstract: Growth performance, forestomach development, and carcass and meat quality of veal calves fed a milk replacer diet (Control) were compared to those obtained from calves fed the same liquid diet plus 250 g x calf(-1) x d(-1) of dried beet pulp or wheat straw. Three groups of 46 Polish Friesian calves, balanced according to initial BW, were assigned to the three dietary treatments in a fattening trial, which lasted 160 d. The provision of either solid feed did not affect the milk replacer intake. However, calves'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
60
5
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 16 publications
13
60
5
1
Order By: Relevance
“…This supports the concept of higher productivity through establishment of a functional rumen at the earliest (Cozzi et al, 2002;Sahoo, Kamra, & Pathak, 2005). This supports the concept of higher productivity through establishment of a functional rumen at the earliest (Cozzi et al, 2002;Sahoo, Kamra, & Pathak, 2005).…”
Section: Ta B L Esupporting
confidence: 84%
“…This supports the concept of higher productivity through establishment of a functional rumen at the earliest (Cozzi et al, 2002;Sahoo, Kamra, & Pathak, 2005). This supports the concept of higher productivity through establishment of a functional rumen at the earliest (Cozzi et al, 2002;Sahoo, Kamra, & Pathak, 2005).…”
Section: Ta B L Esupporting
confidence: 84%
“…Production system had no significant effect on sensory properties of meat, in agreement with observations of Bergström and Dijkstra (1991), Johnson et al (1992), Cozzi et al (2002) and Xiccato et al (2002), who compared exclusively milk-fed calves with alternatively fed calves. Vieira et al (2004) reported differences in juiciness and acceptability, relating them to variations in intramuscular fat content.…”
Section: Discussionsupporting
confidence: 79%
“…However, when weight gains in the finishing period were studied on monthly intervals, no differences were observed between TWNS and TWS calves (data not shown). In fact, Cozzi et al (2002) found no differences in the length of papillae of ruminal mucosa due to the provision of solid feeds to milk-fed calves. Moreover, Myers et al (1999) studied the effect of pre-weaning concentrate feeding in traditionally weaned calves and reported no effects in both digestive morbidity and weight gains, which contradicted Fluharty and Loerch (1996), who reported that pre-weaning solid feeding decreased digestive morbidity.…”
Section: Discussionmentioning
confidence: 74%